Criminal Policy Preferences Among the Public and the Police: A Comparison - Visschers, Jonas (International criminal justice review, 2025)
Through surveys in Flanders (Belgium), the article investigates the criminal policy preferences of the public and the police, a topic of considerable policy relevance that has so far received limited academic attention. It describes and compares such preferences both for specific crimes, within the realm of the criminal justice (CJ) process, and in general, considering interventions that reflect the broadening scope of contemporary criminal policy. Data from 2,348 citizens and 381 police officers point to the capability of both groups to discriminate, that is, to support different CJ interventions depending on the crimes considered, and shows that, for most crimes, the public backs more lenient interventions than the police. Instead, both groups’ general criminal policy preferences are quite similar.